Iron- and Zinc-Fortified Lentil (Lens culinaris Medik.) Demonstrate Enhanced and Stable Iron Bioavailability After Storage - Podder, Rajib; Glahn, Raymond P.; Vandenberg, Albert (Frontiers in Nutrition, 2021)
Lentil (Lens culinaris Medik) is a quick-cooking, rapidly expanding protein-rich crop with high iron (Fe) and zinc (Zn), but low bioavailability due to the presence of phytate, similar to other grains. Lentils dual-fortified with Fe and Zn can significantly improve the bioavailable Fe and Zn content. Three milled lentil product types (LPTs) were fortified with Fe using NaFeEDTA ethylenediaminetetraacetic acid iron (iii) sodium salt) (Fe-fortified) or Zn from ZnSO4.H2O (Zn-fortified) or both (dual-fortified). Fe, Zn, phytic acid (PA) concentration, and relative Fe bioavailability (RFeB%) were assessed for samples from two fortified batches (initial and for one-year stored). Fe, Zn, and RFeB% were increased significantly in two batches of samples from the three LPTs, and decreased by 5-15% after one year of storage. PA concentration decreased from 8-15% after fortification of all samples from two batches of the three LPTs but showed different patterns of influence after storage. Dual-fortified lentil fortified with 24 mg Fe and 12 mg Zn.100-1g lentil had the highest amount of Fe and Zn, the lowest PA concentration, and RFeB% was increased from 91.3 to 519.5%. Significant (p ≤ 0.01) Pearson correlations were observed between Fe concentration vs. PA:Fe molar ratio (MR), Fe concentration vs. RFeB%, RFeB% vs. PA:Fe MR, and Zn concentration vs. PA:Zn MR in all samples from two batches of the three LPTs. In conclusion, dual-fortified lentil can contribute significant bioavailable Fe and Zn to populations at risk of Fe and Zn deficiency.